PENGARUH KEPERCAYAAN, REPUTASI, NORMA TIMBAL BALIK DAN HUBUNGAN YANG DIHARAPKAN TERHADAP PERILAKU BERBAGI PENGETAHUAN DI MEDIA SOSIAL: Dibuat Oleh Panca Kurniati, Muhammad Fithrayudi Triatmaja - Panca Kurniati; muh Fithrayudi Triatmaja (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
This study was aimed to examine the effect of trust, reputation, norm of reciprocity and expected relationships to knowledge sharing behavior on social media. The population in this study were lecturers at Universitas Muhammadiyah Pekajangan Pekalongan (UMPP). The non-probability determination method in this research is purposive sampling. Hypothesis and variable testing using multiple linear regression analysis based on the data obtained was carried out with the help of the SPSS 26 statistical program for windows. The research findings show that trust, reputation, and reciprocal norms do not have a positive effect on knowledge sharing behavior on social media. However, the expected relationship has a positive and significant effect on knowledge sharing behavior on social media. This is because the greater the relationship expected by individuals on social media, the greater the encouragement of individuals to share knowledge online.